Export market opportunities for the rural economy within the context of the FTAA, WTO, AND CSME - Watson, Noel ([s.n.] [S.l.], 2002)
Examines briefly, the likely impact and benefits of liberalization on the relatively small, vulnerable CARICOM economies. Outlines the critical components of export marketing.